O uso dos resultados do Saeb no sistema municipal de Educação de Ipecaetá-BA - Silveira, Lucivane Oliveira de Santana (2025)
The Basic Education Assessment System (SAEB) plays a central role in Brazil's educational policies. Researchers in the educational field highlight the importance of SAEB results in the formulation and implementation of public educational policies. In particular, studies focus on how these results are used to influence and direct decisions in the educational field. Based on this, discussions held on the topic highlight the relevance of the instrument in improving the quality of education in Brazil. Therefore, this study sought to understand how the use of the results of large-scale educational assessments from SAEB contributes to the quality of education in the municipality of Ipecaetá-BA. The research methodology adopted for this study was the qualitative approach, which allows for an in-depth understanding of thetopic and the analysis of the experiences and perceptions of those involved. In addition, a descriptive and exploratory method was used, using techniques of document analysis and interviews with school administrators of final years of elementary school. Through this process, we identified that the municipality does not use the results of the Saeb assessments as an instrument in the construction of public policies, nor in improving the quality of education, being absent in the official documents that govern the education of the municipality, as well as in the actions of school management, which, in turn, indicates the need to invest in the training of school management professionals on the subject.